Avaliação de proficiência oral em língua estrangeira : foco nos elementos provocadores na interação face a face do exame Celpe-Bras - Faria, Elaine Risques (2017)
Proficiency exams and tests have increasingly attracted the attention of people in general and Applied Linguistics researchers interested in Language Assessment, as they may cause a significant impact on the examinee, since the results may lead to decisions and consequences in relation to their professional and / or educational life, such as being accepted into universities or being hired by a company, for example. Due to these factors, these exams and tests, also called ‘high stakes tests’, need studies that reflect on the aspects involved in such exams and tests in order to contribute to their improvement. In this sense, and considering the importance the Certificate of Proficiency in Portuguese Language for Foreigners (Celpe-Bras) has been acquiring over the years, this research investigated the prompts, pictures used to stimulate the conversation between the examiner-interlocutor and the examinee in the Oral Part of Celpe-Bras, called Face to Face Interaction. We developed a qualitative interpretive research, in which questionnaires answered by examinees and examiner-interlocutors from the second edition of Celpe-Bras 2014, the audios of the interviews of an Application Center in Brazil, from the same edition, as well as the prompts used in the interactions and their scripts were analyzed. From the analysis of the data we reflected on how much the prompts operationalize the construct of the Exam; on the participants’ perception of this research, examiner-interlocutors and examinees, regarding the prompts and on how the prompts contribute or not to the performance of the examinees in the Face to Face Interaction. We concluded with some suggestions for the improvement of the oral part of the Exam, especially in relation to the elaboration and use of the prompts and to the standardization of the Manuals and Guidelines of the Celpe-Bras Exam.